2021
DOI: 10.1111/hae.14306
|View full text |Cite
|
Sign up to set email alerts
|

The SLIM study—Shared medical appointments to change lifestyles of overweight people with haemophilia: A randomized multiple baseline (n‐of‐1) design

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The Charge 3 model was one of Fitbit's most recent products when this study was conducted. Lately, Fitbit devices have been used in published research involving PWH 12–16 . These devices are also being utilised in ongoing studies in the haemophilia population, among others to measure PA endpoints in interventional studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Charge 3 model was one of Fitbit's most recent products when this study was conducted. Lately, Fitbit devices have been used in published research involving PWH 12–16 . These devices are also being utilised in ongoing studies in the haemophilia population, among others to measure PA endpoints in interventional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Fitbit devices have been used in published research involving PWH. [12][13][14][15][16] These devices are also being utilised in ongoing studies in the haemophilia population, among others to measure PA endpoints in interventional studies. It is therefore necessary to evaluate the accuracy of these monitors in measuring the PA of PWH.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the selected studies. Three studies were conducted in the USA [ 26 , 27 , 28 ] and one each in Greece [ 29 ], China [ 30 , 31 ], The Netherlands [ 32 ], and Scotland [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our age inclusion criterion was studies in adults (i.e., defined as ≥18 years), but for Kwasnika et al, as only one of 25 participants was aged in the 16 to 20 years group, we decided to include this paper [ 33 ]. Three studies included males only [ 26 , 29 , 32 ], and of the studies that included both genders, all had females as the majority [ 27 , 28 , 30 , 33 ]. Four studies reported the baseline BMI of participants, which ranged from 17.2–44 kg/m 2 [ 28 , 29 , 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation